Low-Wage Import Competition, Inflationary Pressure, and Industry Dynamics in Europe - Raphael Auer; Kathrin Degen; Andreas M. Fischer (Swiss National Bank, Study Center Gerzensee, 2011)
What is the impact of import competition from low-wage countries (LWCs) on inflationary pressure in Europe? This paper examines whether labor-intensive exports from emerging Europe, Asia, and other global regions have a uniform impact on producer prices in Germany, France, Italy, Sweden, and the United Kingdom. In a panel covering 110 (4-digit) NACE industries from 1995 to 2008, instrumental variable estimations predict that LWC import competition is associated with strong price effects. More specifically, when LWC exporters capture 1% of European market share, producer prices decrease by about 3%. In contrast, no effect is present for import competition from low-wage countries in Central and Eastern Europe. Decomposing the mechanisms that underlie the LWC price effect on European industry, we show that import competition has a pronounced effect on average productivity with only a muted effect on wages or margins. Owing to the exit of firms and the increase in productivity, LWC import competition is shown to have substantially reduced employment in the European manufacturing sector.
Keywords: F11; F12; F14; F16; F40; 330; intra-industry trade; comparative advantage; globalization; Intraindustrieller Handel; Komparativer Vorteil; Globalisierung; Standortwettbewerb; Europa